2016
DOI: 10.1007/s13762-016-1077-1
|View full text |Cite
|
Sign up to set email alerts
|

Release and toxicity comparison between industrial- and sunscreen-derived nano-ZnO particles

Abstract: Many consumer products containing ZnO have raised concern for safety in regard to environmental impact and the public health. Widely used sunscreens for protecting against UV and avoiding sunburns represent a great exposure to nano-ZnO, one of the ingredients commonly applied in sunscreens. Applying nanoproducts on beaches may release nanoparticles unintentionally into the ocean. Despite the accumulation of such nanoproducts in the ocean harming or being detrimental to critical marine organisms, few studies ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Previous results have suggested that the physical interactions of NPs induce significant oxidative stress, which provides direct evidence for the toxicological impact of engineered raw NPs in aquatic organisms [128,135]. In general, both sunscreen-derived and raw NPs can undergo photooxidation and generate ROS under sunlight irradiation, and ROS overgeneration is deemed to result in subsequent cell membrane damage, lipid peroxidation, growth inhibition, and other negative impacts [103,141,142]. Sunscreen-derived nTiO 2 has been indicated to induce the photocatalytic generation of ROS, such as H 2 O 2 , in vitro and cause growth inhibition and distribution changes in algae [9,103,104,143].…”
Section: Potential Mechanisms For the Toxicity Of Sunscreen-derived I...mentioning
confidence: 95%
See 1 more Smart Citation
“…Previous results have suggested that the physical interactions of NPs induce significant oxidative stress, which provides direct evidence for the toxicological impact of engineered raw NPs in aquatic organisms [128,135]. In general, both sunscreen-derived and raw NPs can undergo photooxidation and generate ROS under sunlight irradiation, and ROS overgeneration is deemed to result in subsequent cell membrane damage, lipid peroxidation, growth inhibition, and other negative impacts [103,141,142]. Sunscreen-derived nTiO 2 has been indicated to induce the photocatalytic generation of ROS, such as H 2 O 2 , in vitro and cause growth inhibition and distribution changes in algae [9,103,104,143].…”
Section: Potential Mechanisms For the Toxicity Of Sunscreen-derived I...mentioning
confidence: 95%
“…Direct toxicology data on the effects of sunscreen-derived inorganic nTiO 2 on zooplankton, fish, and benthos are rare [49,[103][104][105][106]. A recent study indicated that nTiO 2 released from sunscreens causes repellency and mortality in shrimp (Palaemon varians) and speculated that the avoidance response might be the main factor responsible for the reduction in the shrimp population due to increasing sunscreen concentrations at the local scale [85].…”
Section: Ntio 2 Uvfsmentioning
confidence: 99%
“…Accordingly, they have been detected in the environment at concentrations of up to 17.1 mg per kg dry mass in sludge (Read et al., 2016). There is increasing concern of their impact in aquatic environments due to the local accumulation and the fact that most aquatic species cannot escape exposure (Spisni, Seo, Joo, & Su, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, there are no current regulations that enforce the integrity of "non-nano" and "reef-safe" advertisement claims, but consumer awareness has recently demanded that manufacturers should be more accurate Sobek, et al [112]. UV filters that seem promising to the health of marine organisms are non-nano TiO 2 and non-nano ZnO, based on their larger particle size and lower solubility rates in seawater Fabrega, et al [111][112][113][114]. Contradicting studies, however, found that non-nano UV filters were more toxic to some marine organisms compared to smaller nanoparticles Wong, et al [108,115].…”
Section: Am J Biomed Sci and Resmentioning
confidence: 99%